2006
DOI: 10.3892/or.15.6.1513
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 cytokine imbalance in meningioma, anaplastic astrocytoma and glioblastoma multiforme patients

Abstract: The balance between Th1 and Th2 cytokines is thought to be an important factor in terms of tumour prognosis. Serum samples from 61 newly diagnosed patients with brain tumours and 50 age-and sex-matched non-tumour controls were analysed by ELISA for circulating levels of interleukin-12 (IL-12p70 and p40) and interleukin-10 (IL-10); pivotal Th1 and Th2 cytokines, respectively. Patients were divided into various groups depending on their histological diagnosis: meningioma (n=11), anaplastic astrocytoma (n=4) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 18 publications
(21 reference statements)
7
33
0
1
Order By: Relevance
“…For example, serum IL-10 level has been previously described as significantly increased in high-grade glioma patients compared with non-tumor control patients (13). Similarly, IL-10 was identified in our study as a serum biomarker that accurately classified GBM patients from controls.…”
Section: Discussionsupporting
confidence: 48%
“…For example, serum IL-10 level has been previously described as significantly increased in high-grade glioma patients compared with non-tumor control patients (13). Similarly, IL-10 was identified in our study as a serum biomarker that accurately classified GBM patients from controls.…”
Section: Discussionsupporting
confidence: 48%
“…In a cohort of primary brain tumors, an imbalance in the systemic IL-12/IL-10 balance as hallmarks of Th1/Th2 cytokine production has been shown. This Th1/Th2 cytokine imbalance in patients with brain tumors is similar to that observed in studies on several other tumor types (Kumar et al, 2006). Currently, it is not known whether the lack of Th1 type response in these tumors is accompanied by elevation in Th17 type of response or not.…”
Section: Introductionsupporting
confidence: 58%
“…Such studies could also address other questions by investigating the circulating helper T cell profile in a large number of glioblastoma patients and correlating it with, not just tumoral 10q status, the parameter analyzed in our report, but with mutations in each of the three specific 10q oncogenes, and with the subsequent development of clinical infections. If our data is elaborated upon in this manner, the fact that the majority of glioblastomas exhibit LOH 10q could explain why the majority of glioblastoma patients exhibit a circulating Th2 rather than Th1 profile, one that promotes humoral immunity against systemic infection but weakens cellular antitumor immunity [19]. Further investigation of the different effects of an oncogene mutation on antitumor cellular versus systemic humoral immunity could provide insight into both antitumor immunity and host defenses against local and systemic infection.…”
Section: Discussionmentioning
confidence: 89%
“…Of note, two-thirds of glioblastoma patients have tumor-secreted cytokines that favor a circulating Th2 profile, while 1/3 of glioblastomas secrete cytokines favoring a Th1 profile [7,8]. One study found that most glioblastoma patients have both elevated circulating levels of interleukin 10, a Th2 promoting cytokine, and reduced circulating interleukin 12, a Th1 promoting cytokine, and that the changes were independent of corticosteroid usage [19]. A similar report found that the Th1-promoting cytokines tumor necrosis factor (TNF) a and interferon (IFN) gamma were reduced in peripheral lymphocytes and glioma cell cultures compared to controls, and that the Th2 promoting cytokines interleukin 4 and interleukin 10 were elevated in peripheral lymphocytes and glioma cell cultures compared to controls [20].…”
Section: Discussionmentioning
confidence: 99%